Beyond Leptin: Emerging Candidates for the Integration of Metabolic and Reproductive Function during Negative Energy Balance - True, Cadence; Grove, Kevin; Smith, M Susan (Frontiers in Endocrinology, 2011)
Reproductive status is tightly coupled to metabolic state in females, and ovarian cycling in mammals is halted when energy output exceeds energy input, a metabolic condition known as negative energy balance. This inhibition of reproductive function during negative energy balance occurs due to suppression of gonadotropin-releasing hormone (GnRH) release in the hypothalamus. The GnRH secretagogue kisspeptin is also inhibited during negative energy balance, indicating that inhibition of reproductive neuroendocrine circuits may occur upstream of GnRH itself. Understanding the metabolic signals responsible for the inhibition of reproductive pathways has been a compelling research focus for many years. A predominant theory in the field is that the status of energy balance is conveyed to reproductive neuroendocrine circuits via the adipocyte hormone leptin. Leptin is stimulatory for GnRH release and lower levels of leptin during negative energy balance are believed to result in decreased stimulatory drive for GnRH cells. However, recent evidence found that restoring leptin to physiological levels did not restore GnRH function in three different models of negative energy balance. This suggests that although leptin may be an important permissive signal for reproductive function as indicated by many years of research, factors other than leptin must critically contribute to negative energy balance-induced reproductive inhibition. This review will focus on emerging candidates for the integration of metabolic status and reproductive function during negative energy balance.